2020
DOI: 10.3390/molecules25184117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Magnetic Nanomaterials with Adsorptive Properties of Arsenic Ions

Abstract: A new synthesis method of hybrid Fe3O4/C/TiO2 structures was developed using microwave-assisted coprecipitation. The aim of the study was to examine the effect of the addition of glucose and titanium dioxide on adsorptive properties enabling removal of arsenic ions from the solution. The study involved the synthesis of pure magnetite, magnetite modified with glucose and magnetite modified with glucose and titanium dioxide in magnetite: glucose: titanium dioxide molar ratio 1:0.2:3. Materials were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Among them, the synthesized magnetite nanoparticles (MNPs) have high As affinity and are magnetically separable. Wojciechowska and Lendzion-Bieluń (2020) confirmed that MNPs prepared by co-precipitation method has a small size and a large specific surface area, and the dose of 2.5 g•L -1 achieved the adsorption degree of 97-99% (initial concentration of As(V): 10 mg•L -1 at pH=7). Partial substitution of MNPs with natural magnetite can avoid the indispensable harmful chemicals used in the synthesis, create mutual benefit in green-adsorbent development and market requirement.…”
Section: Introductionsupporting
confidence: 57%
“…Among them, the synthesized magnetite nanoparticles (MNPs) have high As affinity and are magnetically separable. Wojciechowska and Lendzion-Bieluń (2020) confirmed that MNPs prepared by co-precipitation method has a small size and a large specific surface area, and the dose of 2.5 g•L -1 achieved the adsorption degree of 97-99% (initial concentration of As(V): 10 mg•L -1 at pH=7). Partial substitution of MNPs with natural magnetite can avoid the indispensable harmful chemicals used in the synthesis, create mutual benefit in green-adsorbent development and market requirement.…”
Section: Introductionsupporting
confidence: 57%
“…Furthermore, the synergetic effect of both iron oxide nanoparticles and GO led to an increase in CLI S BET three times. This increase could be ascribed to the large surface area of the coated materials (MAG~80 m 2 g −1 ; GO~400 m 2 g −1 ) [ 54 , 55 ]. The same trend was observed for the V tot .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the pore size distribution of pure magnetite (Fe 3 O 4 ) and magnetite modified with titanium dioxide in different molar ratios (Fe 3 O 4 /C/TiO 2 ). Nanocrystalline magnetite is a mesoporous material, with a pore size in the range of 5–15 nm [ 12 ]. The modification with titanium dioxide caused the pore size to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…A full-pattern fit based on the Rietveld refinement was used to calculate the weight fractions of the identified crystallographic phases. The Scherrer equation was used to determine the size of magnetite and anatase crystallites [ 11 , 12 , 13 ]: where D is the crystallite size, k is the dimensionless shape factor, is the X-ray wavelength, is the line broadening at half maximum intensity, and is the Bragg angle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation